(untitled) (Itinera, 2025)
This paper investigates the relationship between biodiversity and aesthetic experience, proposing an unconventional approach to understand the biological diversity in philosophical terms. The most widely shared perspective in contemporary Environmental Aesthetics emphasises the importance of preserving biological diversity, considering the aesthetic value of beauty one of the pillars for the defence of the diversity of life forms on our planet. The perspective proposed here distances itself from this approach. In fact, this article questions whether we can imagine an aesthetic experience of biodiversity that surpasses the mere appreciation of the beauty of individual animal and plant species; instead, it encourages a focus on the grandeur of biodiversity itself, highlighting its sublime nature. In the first part of this article, we will examine the idea of aesthetic experiences related to biodiversity, outlining the theoretical standpoint that informs our argument (paragraph 1); then we will briefly analyze the different aesthetic relationship that beauty and the sublime establish with natural entities (paragraph 2). Particular attention will be given to the historical interpretation of the sublime given by Immanuel Kant in the Critique of Judgement, especially in the section dedicated to the Analytic of Sublime (paragraph 3). In the second part of the article, we will finally discuss the significance of the sublime in the context of the current ecological crisis and in relation to the global loss of biodiversity. We believe that an appreciation of the aesthetics of the sublime can improve our commitment to preserving biological diversity, not only by evoking feelings of wonder and respect for nature but also by revealing the complexity and fragility of the living networks of which we are part.